PLATYNG OF WEAR RESISTANT SURFACE LAYERS BY THE METHOD - LASER SINTERING - CIOFU Florin; NIOATA Alin (Fiabilitate şi Durabilitate)
The essence of process for production of metal powders by aggregation is the formation and sintering operations that cause growth and stabilization of the contact surfaces, together with connections interatomic cohesion between particles. A body of metal powders is a thermodynamically unstable state due to the smoothness powder, grains surface roughness, form, degree of hardening in deformed areas, surface defects at grain polycrystalline networks (vacations, dislocations), etc.